A PASSIVELY MODE-LOCKED CR4+:FORSTERITE LASER WITH ELEСTRONICALLY CONTROLLED OUTPUT CHARACTERISTICS - S. A. Zolotovskaya; K. G. Wilcox; A. Abdolvand; D. A. Livshits; E. U. Rafailov (Приборы и методы измерений)
Applicability of electronic control of laser output parameters to bulk solid-state laser sources is demonstrated. A single laser source with variable pulse duration for novel imaging and manipulation systems is presented. Stable passive mode-locking of a Cr4+:forsterite laser using a voltage controlled p-n junction quantum dot saturable absorber was achieved. Output shortening from 17,4 to 6,4 ps near-transform limited pulses was obtained by applying reverse bias.